2020
DOI: 10.1016/j.celrep.2020.108310
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin-2 Regulates Postsynaptic Cytoskeleton Organization and Neuromuscular Junction Development

Abstract: Highlights d Dyn2 promotes the maturation and turnover of podosomes d The actin-bundling activity of Dyn2 is regulated by Srcmediated phosphorylation d Centronuclear myopathy-linked Dyn2 mutants display abnormal actin-organizing activities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 76 publications
2
31
0
Order By: Relevance
“…In accordance with this idea, Lin and collaborators recently demonstrated that dynamin-2 regulates the bundling of actin at the postsynaptic membranes of neuromuscular junctions (NMJs). Remarkably, CNM-linked mutations seem to disrupt this dynamin-2 function impairing actin remodeling and perturbing postsynaptic structures at the NMJs (Lin, et al, 2020). A similar mechanism could be operating at central excitatory synapses in the brain of HTZ mice, explaining the defects that we observed in dendritic spine morphology, synaptic transmission and cognitive functions.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In accordance with this idea, Lin and collaborators recently demonstrated that dynamin-2 regulates the bundling of actin at the postsynaptic membranes of neuromuscular junctions (NMJs). Remarkably, CNM-linked mutations seem to disrupt this dynamin-2 function impairing actin remodeling and perturbing postsynaptic structures at the NMJs (Lin, et al, 2020). A similar mechanism could be operating at central excitatory synapses in the brain of HTZ mice, explaining the defects that we observed in dendritic spine morphology, synaptic transmission and cognitive functions.…”
Section: Discussionsupporting
confidence: 52%
“…This latter seem to rely on defects in the actin cytoskeleton organization. As the catalytic activity of dynamin-2 is an important regulator of the actin dynamics (Mooren, et al, 2009;Gu, et al, 2010;Yamada, et al, 2013;Yamada, et al, 2016;Lin, et al, 2020) and this is a mechanism affected in dynamin-2 linked CNM (González-Jamett, et al, 2017) these data strongly suggest that CNM-causing mutations perturb the synaptic role of dynamin-2, impacting on the actin-dependent dendritic-spine structure and consequently affecting synaptic transmission and cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that ArhGef5, a Guanine nucleotide-exchange factor (GEF) for Rho GTPases, is involved in NMJ stability [33]. Moreover, in vitro maturation of AChR clusters is accompanied by the formation of synaptic podosomes, rich in actin and various actin-binding proteins, such as Arp2, Tks5, cortactin, dynamin, filamin, and angiomotin-like 2 (Amotl2) [18,34,35]. Knockdown of Amotl2, a member of the angiomotin family, impacts both organization of the AChR clusters and the structure of synaptic podosomes in myotubes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of Amotl2, a member of the angiomotin family, impacts both organization of the AChR clusters and the structure of synaptic podosomes in myotubes [18]. Recent studies showed that microtubule-asssociated GTPase, dynamin2, is essential for podosome and cluster perforation dynamics and the organization of postsynaptic cytoskeleton at Drosophila NMJs [35]. Apart from the actin cytoskeleton, the high-density specialized microtubule network plays an important role in the postsynaptic machinery [36,37].…”
Section: Introductionmentioning
confidence: 99%